ANALYSIS OF RICE FIELD SOIL FERTILITY IN COASTAL GEOGRAPHICAL AREAS: A CASE STUDY OF SITUBONDO DISTRICT, JAWA TIMUR PROVINCE, INDONESIA: ANALISIS KESUBURAN TANAH SAWAH DI WILAYAH GEOGRAFIS PESISIR: STUDI KASUS KABUPATEN SITUBONDO - romadhona, sukron; Arifandi, Josi Ali (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2024)
Soil fertility is a key factor in agricultural success, especially in rice fields, which are the main source of rice production. The research results showed significant variations in the physical and chemical properties of soil in the rice fields, which were the focus of the research. P2O5 for rice fields in Situbondo district is in the range of values from 19.34 me/100g to 142.29 me/100g, dominated by very high status. The distribution of K2O in the rice fields of Situbondo district is in the range of values from 16.95 me/100g to 395.99 me/100g, including low to very high status. The distribution of K2O is dominated by very high states. The distribution of organic C in rice field soil in Situbondo district is in the range of 0.93% to 6.54%. The organic C content is dominated by medium status. The KTK of Situbondo Regency is in the range of values from 10.18 me/100g to 48.23 me/100g. The KTK value is dominated by high status. Base saturation in the study area is classified as low to high, ranging from 19.43% - 78.89% and is dominated by status.